2005
DOI: 10.2466/pr0.96.1.163-166
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use by Psychiatric Inpatients

Abstract: 82 psychiatric inpatients hospitalized for acute care were interviewed about their use of complementary and alternative medicine (CAM) modalities. The clinical diagnoses of respondents included Depressive Disorder (61%), Substance Abuse (26%), Schizophrenia (9%), and Anxiety Disorders (5%). Analysis indicated that 63% used at least one CAM modality within the previous 12 mo. The most frequently used modality was herbal therapies (44%), followed by mind-body therapies such as relaxation or mental imagery, hypno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(45 citation statements)
references
References 5 publications
2
42
0
1
Order By: Relevance
“…There exists a growing body of research that explores the benefits of using yoga, meditation, and/or other Eastern body-based interventions in clinical facilities serving psychiatric populations (Davis, Strasburger, & Brown, 2007;Elkins, Rajab, & Marcus, 2005;Kozasa et al, 2008;Weiser, Kutz, I., Kutz, S., & Weiser, 1995). Some studies have shown that there are significant improvements in mood and anxiety symptoms of psychiatric patients after participating in yoga or meditation (Davis et al, 2007;Kozasa et al, 2008;Lavey et al 2005), and modest improvements were revealed in a 4-month study of yoga therapy as an add-on treatment in patients experiencing schizophrenia (Duraiswamy et al, 2007).…”
Section: Yoga and Severe Mental Illnessmentioning
confidence: 99%
“…There exists a growing body of research that explores the benefits of using yoga, meditation, and/or other Eastern body-based interventions in clinical facilities serving psychiatric populations (Davis, Strasburger, & Brown, 2007;Elkins, Rajab, & Marcus, 2005;Kozasa et al, 2008;Weiser, Kutz, I., Kutz, S., & Weiser, 1995). Some studies have shown that there are significant improvements in mood and anxiety symptoms of psychiatric patients after participating in yoga or meditation (Davis et al, 2007;Kozasa et al, 2008;Lavey et al 2005), and modest improvements were revealed in a 4-month study of yoga therapy as an add-on treatment in patients experiencing schizophrenia (Duraiswamy et al, 2007).…”
Section: Yoga and Severe Mental Illnessmentioning
confidence: 99%
“…3,5,6 Approximately 44% of psychiatric inpatients have used an herbal preparation to treat a variety of symptoms. 7 Egg components have a variety of physiologic effects, including novel antimicrobial, immunomodulatory, anticancer, and antihypertensive activities; antioxidant properties; protease-inhibiting ability; and nutrient bioavailability. 8 The isolate investigated in the current study, Young Tissue Extract (YTE Ò ; Med-Eq AS, Tonsberg, Norway), is extracted from fertilized, partially incubated hen eggs.…”
Section: Introduction Dmentioning
confidence: 99%
“…[54][55][56][57][58][59][60] CAMs are more commonly used by those with psychiatric disorders especially patients with anxiety, depression and insomnia. [61][62][63] CAMs have shown to improve sleep in 4.5% of insomnia patients translating to 1.6 million U.S. citizens. 64 Herbal supplements or nutritional medicine, tai chi, and yoga are the most common CAMs utilized with 56% of patients reporting that CAMs were important in maintaining their health and 72% thought there was a significant improvement in their insomnia symptoms.…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%